Manajemen Risiko, Pengelolaan Dana Dan Pentingnya Lembaga Penjamin Simpanan Dalam Koperasi Simpan Pinjam di Indonesia - Rahel Veronika; Yohana Feby; Gustina Sari; Hasyim Hasyim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study emphasizes the functions of the Indonesian Deposit Insurance Corporation (Lembaga Penjamin Simpanan, LPS) in savings and loan cooperatives (KSP), such as managing funds and managing risks. KSPs play an important role in the micro economy, especially in providing financial access to people who are not served by banks and other formal financial institutions. This research employs a qualitative methodology and uses a literature review approach. A qualitative approach was chosen as it allows for a more in-depth understanding of the complex issues of risk management, fund management, and deposit insurance functions in savings and loan cooperatives in Indonesia. To ensure the viability and health of this sector that aims to make a significant contribution to financial inclusion and inclusive economic growth, the government, financial institutions, and cooperatives must work together. To advance the savings and loan cooperative sector in Indonesia, strategic measures should be taken, such as improving risk management and supporting IDICs. Ultimately, this will support the stability of the national financial system and the economic well-being of people in Indonesia.